THE TEACHING CONCEPTION IN AN INCLUSIVE CHILD EDUCATION EXPERIENCE: A CASE STUDY - Salto, Mariana Picchi [UNESP]; Carbone Carneiro, Relma Urel [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2019)
With the effectiveness of inclusive child education, the conditions necessary for children to fully develop are made available, as is the formation of a new generation, free of prejudgments over the other. In this context, through a case study, the present research had as general objective to investigate if the pedagogical work contributes to the inclusive education of a student with the Cri du Chat syndrome. For this, a semi-structured interview was performed with a pedagogue, from the municipal teaching network, in a city in the interior of Sao Paulo. The data were analyzed according to the content analysis. It is concluded that teacher training for inclusive education is still very precarious, which means that teachers are unable to act in order to ensure inclusion in the classroom.
Keywords: Inclusive education; Child education; Teaching conceptions